Non-cooperative game theory as a decision-making tool in conflict situations and asymmetric information - Mohamed, Osman Abdel Ghani (Fakulti Sains dan Teknologi, 2010)
The main purpose of this research is to study non-cooperative game theory as strategic decision making tool in conflict situations, with describing how to find solution to these models and to analyze asymmetric information.The objective of dealing with the problem of decision making in conflict situations is to find optimal strategy among alternative strategies. Two approaches will be put into consideration; The mathematical modeling of the situation and computational solutions for these models.